Association Between Preanalytical Factors and Tumor Mutational Burden Estimated by Next‐Generation Sequencing‐Based Multiplex Gene Panel Assay. (11th June 2019) - Quy, Pham Nguyen; Kanai, Masashi; Fukuyama, Keita; Kou, Tadayuki; Kondo, Tomohiro; Yamamoto, Yoshihiro; Matsubara, Junichi; Hiroshima, Akinori; Mochizuki, Hiroaki; Sakuma, Tomohiro; Kamada, Mayumi; Nakatsui, Masahiko; et al.
Abstract: Background: Tumor mutational burden (TMB) measured via next‐generation sequencing (NGS)‐based gene panel is a promising biomarker for response to immune checkpoint inhibitors (ICIs) in solid tumors. However, little is known about the preanalytical factors that can affect the TMB score. Materials and Methods: Data of 199 patients with solid tumors who underwent multiplex NGS gene panel (OncoPrime), which was commercially provided by a Clinical Laboratory Improvement Amendments‐licensed laboratory and covered 0.78 megabase (Mb) of capture size relevant to the TMB calculation, were reviewed. Associations between the TMB score and preanalytical factors, including sample DNA quality, sample type, sampling site, and storage period, were analyzed. Clinical outcomes of patients with a high TMB score (≥10 mutations per megabase) who received anti‐programmed cell death protein 1 antibodies ( n = 22) were also analyzed. Results: Low DNA library concentration (<5 nM), formalin‐fixed paraffin‐embedded tissue (FFPE), and the prolonged sample storage period (range, 0.9–58.1 months) correlated with a higher TMB score. After excluding low DNA library samples from the analysis, FFPE samples, but not the sample storage period, exhibited a marked correlation with a high TMB score. Of 22 patients with a high TMB score, we observed the partial response in 2 patients (9.1%). Conclusion: Our results indicate that the TMB score estimated via NGS‐based gene panel could be affected by the DNA library concentration and sample type. These factors could potentially increase the false‐positive and/or artifactual variant calls. As each gene panel has its own pipeline for variant calling, it is unknown whether these factors have a significant effect in other platforms. Implications for Practice: A high tumor mutational burden score, as estimated via next‐generation sequencing‐based gene panel testing, should be carefully interpreted as it could be affected by the DNA library concentration and sample type. Abstract : Little is known about the preanalytical factors that could affect the tumor mutational burden score from next‐generation sequencing‐based multiplex gene panels, a promising biomarker to predict response to immune checkpoint inhibitors. This article investigates the association.